High temperature low cycle fatigue characterization of equiaxed MAR-M-247. (June 2019) - Maggiani, G.; Roy, M.J.; Colantoni, S.; Withers, P.J.; Stramare, S.; Monti, C.; Bernardini, L.
Highlights: The paper extends the temperature range of LCF data for MAR-M-247 up to 1038  ° C. To our knowledge, a novel approach considering the mean compressive stress effects was employed to define LC model parameters. The parameters for both kinematic and isotropic hardening models have been identified and optimized for gas turbine representative strain ranges, extending the available literature data. It has been demonstrated that through an optimization process of parameters, the LC model defined at a specific strain range can be applied to predict the cyclic response of different strain ranges. Abstract: Low cycle fatigue tests have been performed at 1038  ° C on equiaxed MAR-M-247 under a mean compressive strain. Strain ranges assessed were 0.4, 0.6 and 0.8%, with this test program reflecting industrial gas turbine duty cycles. Fractographic analysis demonstrated transgranular crack propagation with intergranular fast fracture. Heavily oxidized secondary cracks were observed throughout. The details of a Lemaitre-Chaboche constitutive model that has been applied to the experimental stress-strain response are described. It was found that this model was capable of capturing both plastic shakedown and kinematic hardening effects with a high degree of accuracy (R 2 up to 0.997 and SSE up to 6E+4). The suitability of extending this model to address different strain histories are detailed.